Reframing Digital Humanities Conversations with Digital Humanists - Chambliss, Julian (Open textbook library., 2021)
Growing from Reframing History, a podcast about history theory and practice, Reframing Digital Humanities: Conversations with Digital Humanists, Julian Chambliss, Professor of English at Michigan State University, brings together a diverse group of digital humanities practitioners to reflect on theory and practice. From the question of public engagement and knowledge production to considerations of identity and cultural production, the conversations presented in this work shed light on the ways digital humanities offer scholars tools to ask humane questions. Are the benefits promised being achieved? Are the right tools and training available? Are we asking the right questions? In this volume, scholars deeply engaged in using digital tools reflect on their work and this dynamic academic field.